The Mediating Effect of Work Engagement in Relation to Technology Readiness Index and Adaptive Performance Among Newly Hired It Employees - Malek, Khadijah Abdul; Shahidan, Athifah Najwani; Arshad, Muhammad Zulqarnain (Politeknik Ilmu Pemasyarakatan, 2023)
This study investigates the mediating effect of work engagement in relation to the Technology Readiness Index (TRI) and adaptive performance among newly hired IT employees. In the contemporary workplace, the successful integration of information technology plays a crucial role in organizational performance. As such, understanding the factors that influence the adaptive capabilities of IT employees becomes paramount. The research will adopt a quantitative approach, utilizing a sample of newly hired IT professionals from diverse industries. The implications of these findings will provide valuable insights for organizations seeking to optimize their IT workforce's performance and adaptability. Fostering a work environment that encourages work engagement, coupled with the promotion of technology readiness, can yield a more agile and responsive IT workforce. Further research opportunities exist to explore the interplay between technology adoption, work engagement, and adaptive behaviors in different organizational contexts